Expression of Ghrelin Receptor mRNA in the Rat and the Mouse Brain - Zigman, Jeffrey M. (J Comp Neurol, 2006)
Ghrelin is a hormone that stimulates growth hormone secretion and signals energy insufficiency via interaction with its receptor, the growth hormone secretagogue receptor (GHSR). The GHSR is located in both the central nervous system and the periphery. Its distribution in the CNS, as assessed by in situ hybridization histochemistry (ISHH), has been described previously in a few mammalian species, although these studies were limited by either the detail provided or the extent of the regions examined. In the present study, we systematically examined the distribution of GHSR mRNA in the adult rat and mouse brains and cervical spinal cords by using ISHH with novel cRNA probes specific for the mRNA encoding functional GHSR (the type 1a variant). We confirmed GHSR mRNA expression in several hypothalamic nuclei, many of which have long been recognized as playing roles in body weight and food intake. GHSR also was found in several other regions previously unknown to express GHSR mRNA, including many parasympathetic preganglionic neurons. Additionally, we found GHSR mRNA within all three components of the dorsal vagal complex, including the area postrema, the nucleus of the solitary tract, and the dorsal motor nucleus of the vagus. Finally, we examined the co-expression of GHSR with tyrosine hydroxylase and cholecystokinin, and demonstrate a high degree of GHSR mRNA expression within dopaminergic, cholecystokinin-containing neurons of the substantia nigra and ventral tegmental area.